IoT Based Dual wavelength Non-Invasive Haemoglobin Sensor System. (October 2019) - Venkata Praveen Kumar, G.; Jagadeesh, B.; Ravi, T.
Abstract: Haemoglobin is main constituent for characterizing the physiological conditions of a body. For pregnant ladies, haemoglobin is the main factor for prevention of risk factors caused due to anaemia and polycythemiavera. This will used during pre screening test for donating blood and to obtain complete blood count. Hb is calculated from invasive technique in which blood samples are taken using needle which causes pain and discomfort, delay is more in analysing and to receive results, it doesn't allow real time monitoring. But an non-invasive test enable painless and obtain real time monitoring. Red and IR LED are passed through the finger, according to the amount of light absorbed by the tissue, remaining transmitted light detected by a photodiode, the haemoglobin levels i.e. Hbo2and HHb can obtained by interpreting the ratio of red to IR. This method allows pain free online patient monitoring with minimum risk of infection and facilitates real time data monitoring allowing immediate clinical reaction to the measured data.